Iron-catalyzed carboazidation of alkenes and alkynes - Xiong, Haigen; Ramkumar, Nagarajan; Chiou, Mong-Feng; Jian, Wujun; Li, Yajun; Su, Ji-Hu; Zhang, Xinhao; Bao, Hongli (Nature communications, 2019)
Carboazidation of alkenes and alkynes holds the promise to construct valuable molecules directly from chemical feedstock therefore is significantly important. Although a few examples have been developed, there are still some unsolved problems and lack of universal methods for carboazidation of both alkenes and alkynes. Here we describe an iron-catalyzed rapid carboazidation of alkenes and alkynes, enabled by the oxidative radical relay precursor t -butyl perbenzoate. This strategy enjoys success with a broad scope of alkenes under mild conditions, and it can also work with aryl alkynes which are challenging substrates for carboazidation. A large number of diverse structures, including many kinds of amino acid precursors, fluoroalkylated vinyl azides, other specific organoazides, and 2 H -azirines can be easily produced. Carboazidation of alkenes and alkynes holds the promise to construct valuable, functionalized molecules. Here, the authors report a general and efficient iron-catalyzed carboazidation of both alkenes and alkynes enabled by t -butyl perbenzoate.